Constitutively active Lyn kinase causes a cutaneous small vessel vasculitis and liver fibrosis syndrome - de Jesus, Adriana A; Chen, Guibin; Yang, Dan; Brdicka, Tomas; Ruth, Natasha M; Bennin, David; Cebecauerova, Dita; Malcova, Hana; Freeman, Helen; Martin, Neil; Svojgr, Karel; Passo, Murray H; et al. (Nature communications, 2023)
Neutrophilic inflammation is a hallmark of many monogenic autoinflammatory diseases; pathomechanisms that regulate extravasation of damaging immune cells into surrounding tissues are poorly understood. Here we identified three unrelated boys with perinatal-onset of neutrophilic cutaneous small vessel vasculitis and systemic inflammation. Two patients developed liver fibrosis in their first year of life. Next-generation sequencing identified two de novo truncating variants in the Src-family tyrosine kinase, LYN, p.Y508*, p.Q507* and a de novo missense variant, p.Y508F, that result in constitutive activation of Lyn kinase. Functional studies revealed increased expression of ICAM-1 on induced patient-derived endothelial cells (iECs) and of β2-integrins on patient neutrophils that increase neutrophil adhesion and vascular transendothelial migration (TEM). Treatment with TNF inhibition improved systemic inflammation; and liver fibrosis resolved on treatment with the Src kinase inhibitor dasatinib. Our findings reveal a critical role for Lyn kinase in modulating inflammatory signals, regulating microvascular permeability and neutrophil recruitment, and in promoting hepatic fibrosis.
Keywords: neutrofily; src-Family Kinases; Dasatinib; skupina kinas odvozených od src-genu; Vasculitis; Inflammation; lidé; zánět; vaskulitida; fosforylace; Neutrophils; Endothelial Cells; dasatinib; Phosphorylation; endoteliální buňky; Humans